Negative outcomes of staged parathyroidectomy using percutaneous laser ablation - Kulmatov, Salokhiddin; Murodullaev, Marufdjon; Karimova, Malika; Djurakulova, Nargiza; Farhodova, Zebiniso; Togaeva, Gulnora Siddikovna (Science and Education, 2024)
The article gives information about negative outcomes of staged parathyroidectomy using percutaneous laser ablation.